JENIS BAHAN BAKU MAKANAN DAN MINUMAN SERTA PEMANFAATANNYA DALAM PRASASTI MASA BALI KUNO ABAD IX-XI - Ekayani, Dewa Ayu (Humanis; Volume 13. No.3. Desember 2015)
Type of raw materials food that consumed by Balinese this time was already mentioned in the inscriptions of ancient Bali. The appearance of the mention of the type of food ingredients can be found in several inscriptions of ancient Bali such as inscription of Bebetin AI and inscription of Trunyan AI.  At the time of ancient Bali several types of food in addition to various types of food consumed is also courtesy as a means of religious ceremonies. The purpose of this study provide direction for the author to the next step on the activities and answering the second issue raised in this research the type of raw materials and utilization of food and beverages based on data inscriptions of ancient Bali period IX-XI century.The theory that use for this study are structural and functional structural closely related to food is a system of natural processes and food culture is a human need that govern the life of the network. This research was conducted by using literature data collection methods, as well as the method of processing data through qualitative analysis. This analysis through three procedures: data reduction, data presentation, and conclusion. Based on the results of analysis showed several types of raw materials food in the   form of staple foods such as rice and green beans, side dishes of meat and fish and types of beverages such as wine. Food elements are interrelated and affect social interaction Ancient Balinese society. Food has an important value in human life from the past to the present.
Keywords: food, inscriptions, ancient Bali Era